Effects of Medicaid coverage on receipt of tobacco dependence treatment among Medicaid beneficiaries with substance use disorder. (30th May 2022) - Patel, Sadiq Y.; Wayne, Geoffrey F.; Progovac, Ana M.; Flores, Michael; Moyer, Margo; Mullin, Brian; Levy, Douglas; Saloner, Brendan; Cook, Benjamin Lê
Abstract: Objective: Individuals with substance use disorder (SUD) smoke cigarettes at a rate that is more than double the rate of the general population. Tobacco dependence treatment (TDT) is effective at reducing smoking, yet it is unclear whether expanding insurance coverage of these services increases TDT use among Medicaid beneficiaries with SUD. Data Source: 2009–2013 Medicaid data in all 50 states and Washington DC. Study Design: We conducted a retrospective analysis of the 2009–2013 de‐identified Medicaid Analytic Extract (MAX) claims for a 100% national sample of fee‐for‐service (FFS) Medicaid adult beneficiaries. Using a difference‐in‐difference‐in‐differences analysis, we assessed the association of full TDT coverage on TDT medication use and tobacco cessation counseling services between beneficiaries with and without SUD. We adjusted for age, sex, race/ethnicity, diagnosis of co‐occurring chronic illness, state tobacco taxes, and state and year fixed effects. Data Collection/Extraction Methods: We excluded patients not continuously enrolled in Medicaid for 12 months during the calendar year, adults aged 65 and older (given their dual enrollment in Medicaid and Medicare), minors aged 12–17, and pregnant women (for whom different TDT coverage policies apply). Principal Findings: We separately modeled the association between full coverage of (1) counseling, (2) over‐the‐counter nicotine replacement therapy, and (3) prescription cessation medications on TDT medication treatment and counseling services. We found that each coverage led to increases in any TDT medication treatment and counseling services for beneficiaries with SUD. The effects of each coverage on medication treatment were greater for beneficiaries with SUD compared to beneficiaries without SUD (ranging from 4.9 to 6.1 percentage point difference). Conclusion: Coverage of tobacco cessation counseling, over‐the‐counter nicotine replacement therapy, and prescription cessation medications holds promise for reducing the wide disparities in rates of smoking between those with and without SUD.